Development of MEPS-UHPLC–MS/MS multistatin methods for clinical analysis. (February 2016) - Vlčková, Hana; Svoboda, Pavel; Novák, Ondřej; Solich, Petr; Nováková, Lucie
Background: Statins are the microsomal 3-hydroxy-3methylglutaryl-coenzyme A reductase inhibitors used for the treatment of hypercholesterolemia. Some recent studies revealed also the extra-lipid effects and anticancer activities. Due to the wide incidence of cancer diseases, the number of studies dealing with anticancer statin activities has grown in recent years. Development of one universal multistatin method will be a very convenient way of providing practical and economical multiple statin analysis.Results/methodology: Fast and sensitive methods for determination of seven clinically relevant statins, their interconversion products and metabolites (17 analytes in total) in biological samples using microextraction by packed sorbent for sample preparation and UHPLC–MS/MS for subsequent analysis were developed and validated. Three MS platforms with different ion sources, transfer optics, collision cell technologies and scan speed parameters were compared.Conclusion: Significant differences among the methods were observed in terms of selectivity and sensitivity. Microextraction by packed sorbent was successful in the extraction of all 17 analytes from biological matrix.